PENGARUH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBINA MELEK POLITIK SISWA SMA NEGERI 2 PURWOKERTO - Elly Hasan Sadeli (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
This research generally aimed to describe the effects of civic learning in nurturing students’ political literacy, and specifically aimed to examine and discover the effects of civic components application that consisted of civic learning and competences toward the level of students’ political literacy. The process of this research was conducted through quantitative approach. The research method used descriptive method of survey technique. From this research results, it could be generally concluded that: First, civic learning through various democratic learning methods that strengthened the effects of civic education in nurturing students’ political literacy. Second, the better quality of students’ civic competences the higher level of students’ political literacy. Third, an effective and meaningful civic competences was directly able to improve students’ political literacy.Key words: civic education and political literacy.